(3GdRgQ GdjGaY Ydi bhd UGMH GdbGehS dG eGfYs - (3eMeO Hf jhSa GdOejGWjs ((3eMehO UObi s)
(3ChdgG (B:s
(3GdMeO ddg GdCMO GdPi HjOg JUQja GdCaYGd hHYO ajbhd eMeO Hf jhSa GdOejGWi GdMfai bO JcQQ GdSDGd ef HYV GdENhGf Yf bhd GdYdGeI GdajQhRCHGOi ai OjHGLg GdeSei HGdbGehS GdeMjW hGdbGHhS GdhSjW s
(3BNQgG (B:s
(3gh ef HGH VQH dchfg jGFi GdYjf hbS Ydi Pdc eG hbY ajg ef fXGFQg adG fWjd HPcQ GdCeKdI hgPG BNQ eG JjSQ LeYg ai gPG GdebGe hGdMeO ddg hdi GdEfYGe hYdi QShdg CaVd GdUdGI hGdSdGe Je HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs